Peran Artificial Intelligence dan Interoperabilitas Data dalam Transformasi Layanan Kesehatan Digital di Indonesia: Literature Review (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Digital health transformation has become an important strategy for strengthening Indonesia’s healthcare system. The development of artificial intelligence and health data interoperability offers opportunities to improve access, efficiency, service quality, and data-driven decision-making. This article aims to examine the role of artificial intelligence and data interoperability in digital health transformation, particularly in the implementation of digital health services in Indonesia through the SATUSEHAT ecosystem. This study used a narrative literature review method by analyzing relevant scientific articles, institutional reports, and policy documents published between 2020 and 2026. Data analysis was carried out using a narrative thematic synthesis approach with 5 main themes. The review shows that artificial intelligence has the potential to support diagnosis, disease risk prediction, clinical decision support, remote patient monitoring, and healthcare service efficiency. Meanwhile, data interoperability serves as a fundamental basis for integrating electronic medical records and enabling data exchange among healthcare facilities. SATUSEHAT plays an important role as a national health data ecosystem that supports standardization and integration of digital health services. However, its implementation still faces challenges related to infrastructure readiness, digital literacy, data security, patient privacy, metadata quality, and regulation. This review emphasizes that successful digital health transformation requires strong data governance, adaptive regulation, and cross-sector collaboration